Assessing Tn5 and sleeping beauty for transpositional transgenesis by cytoplasmic injection into bovine and ovine zygotes - Bevacqua, Romina Jimena; Fernández y Martin, Rafael; Canel, Natalia Gabriela; Gibbons, Alejandro Eduardo; Texeira, D.I.A.; Lange, F.; Vans Landschoot, Geraldina; Savy, Virginia; Briski, Olinda; Hiriart, María Inés; Grueso, Esther; Ivics, Zoltán; et al. (2017)
Transgenic domestic animals represent an alternative to bioreactors for large-scale production of biopharmaceuticals and could also provide more accurate biomedical models than rodents. However, their generation remains inefficient. Recently, DNA transposons allowed improved transgenesis efficiencies in mice and pigs. In this work, Tn5 and Sleeping Beauty (SB) transposon systems were evaluated for transgenesis by simple cytoplasmic injection in livestock zygotes. In the case of Tn5, the transposome complex of transposon nucleic acid and Tn5 protein was injected. In the case of SB, the supercoiled plasmids encoding a transposon and the SB transposase were co-injected. In vitro produced bovine zygotes were used to establish the cytoplasmic injection conditions. The in vitro cultured blastocysts were evaluated for reporter gene expression and genotyped. Subsequently, both transposon systems were injected in seasonally available ovine zygotes, employing transposons carrying the recombinant human factor IX driven by the beta-lactoglobulin promoter. The Tn5 approach did not result in transgenic lambs. In contrast, the Sleeping Beauty injection resulted in 2 lambs (29%) carrying the transgene. Both animals exhibited cellular mosaicism of the transgene. The extraembryonic tissues (placenta or umbilical cord) of three additional animals were also transgenic. These results show that transpositional transgenesis by cytoplasmic injection of SB transposon components can be applied for the production of transgenic lambs of pharmaceutical interest.